Factors Influencing the Antibacterial Activity of Chitosan and Chitosan Modified by Functionalization - Ardean, Cristina; Davidescu, Corneliu Mircea; Nemeş, Nicoleta Sorina; Negrea, Adina; Ciopec, Mihaela; Duteanu, Narcis; Negrea, Petru; Duda-Seiman, Daniel; Musta, Virgil (International journal of molecular sciences, 2021)
The biomedical and therapeutic importance of chitosan and chitosan derivatives is the subject of interdisciplinary research. In this analysis, we intended to consolidate some of the recent discoveries regarding the potential of chitosan and its derivatives to be used for biomedical and other purposes. Why chitosan? Because chitosan is a natural biopolymer that can be obtained from one of the most abundant polysaccharides in nature, which is chitin. Compared to other biopolymers, chitosan presents some advantages, such as accessibility, biocompatibility, biodegradability, and no toxicity, expressing significant antibacterial potential. In addition, through chemical processes, a high number of chitosan derivatives can be obtained with many possibilities for use. The presence of several types of functional groups in the structure of the polymer and the fact that it has cationic properties are determinant for the increased reactive properties of chitosan. We analyzed the intrinsic properties of chitosan in relation to its source: the molecular mass, the degree of deacetylation, and polymerization. We also studied the most important extrinsic factors responsible for different properties of chitosan, such as the type of bacteria on which chitosan is active. In addition, some chitosan derivatives obtained by functionalization and some complexes formed by chitosan with various metallic ions were studied. The present research can be extended in order to analyze many other factors than those mentioned. Further in this paper were discussed the most important factors that influence the antibacterial effect of chitosan and its derivatives. The aim was to demonstrate that the bactericidal effect of chitosan depends on a number of very complex factors, their knowledge being essential to explain the role of each of them for the bactericidal activity of this biopolymer.